1997
DOI: 10.1530/jrf.0.1110029
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological basis of human Fallopian tubal fluid formation

Abstract: A preparation for the maintenance of human Fallopian tubal epithelial cells as a polarized layer in primary culture was used to study the electrophysiological basis of tubal fluid formation in terms of the movement of Na+, K+ and Cl- ions. Transepithelial potential difference (PD) and short-circuit current (Iscc) were recorded by mounting the epithelial cells in a modified Ussing chamber. Resistance (R) was calculated from the measurements of PD and Iscc. The epithelia, although confluent, formed a 'leaky' ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…First, the epithelial cells have to be isolated from sexually immature mouse uteri in order to enable proliferation in culture, which may not have the same gene expression profile as in mature mice. Secondly, some protein expression or function may be lost during the culture as observed in many cell cultures including human fallopian tubule cells (Downing et al 1997). Most importantly, the culture condition cannot reproduce the cyclic characteristics normally observed in vivo, considering the fluctuating levels of ovarian hormones.…”
Section: Discussionmentioning
confidence: 99%
“…First, the epithelial cells have to be isolated from sexually immature mouse uteri in order to enable proliferation in culture, which may not have the same gene expression profile as in mature mice. Secondly, some protein expression or function may be lost during the culture as observed in many cell cultures including human fallopian tubule cells (Downing et al 1997). Most importantly, the culture condition cannot reproduce the cyclic characteristics normally observed in vivo, considering the fluctuating levels of ovarian hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The spermatozoa then free themselves from the oviductal reservoir and, ultimately, hyperactivation causes a whiplashlike flagella beating, which helps penetration of the egg vestments. ATP is known to act as a signaling molecule on ciliated airway and oviduct epithelium, increasing cilary beat frequency via a calcium-dependent pathway (Barrera et al, 2004;Stutts et al, 1992), and ATP added apically or basally to oviduct epithelial cells can modulate the formation of oviductal fluid (Downing et al, 1997). As well as providing energy for the spermatozoa to swim to the site of fertilization in the oviduct, ATP may, therefore, be acting as a signaling molecule, increasing ciliary beat frequency and helping move the spermatozoa through the oviduct or release them from the oviductal reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Where blockers of histamine receptors or ion channels were used, the cells were incubated in the presence of the blocker on both apical and basal bathing medium for 20 min prior to addition of histamine. The effect of the blockers of ion channels on PD and I scc have been shown previously [6].…”
Section: Epithelial Cell Culturementioning
confidence: 85%
“…Immunocytochemical analyses demonstrated that a pure population of epithelial cells were isolated and that the cells formed extensive desmosome junctions in culture. We have subsequently shown that the movement of chloride ions is an important factor in the generation of the transepithelial potential difference across these cultured human oviductal epithelial cells and that extracellular ATP is a potent modulator of electrophysiological activity [6].…”
Section: Introductionmentioning
confidence: 96%